Fenomena Rekrutmen Artis Anggota Legislatif Ditinjau dari Perspektif Teori Partai Politik - Resty Nabilah; Izomiddin Izomiddin; Raegen Harahap (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
The phenomenon of artists entering the world of politics or becoming a legislative candidate has been happening for a long time. Since the election during the New Order era, several artists have sat in Senayan representing the group's envoy faction, which consists of artists and religious figures. In this reform era, a number of celebrities have even become candidates for legislative members registered by political parties. Political parties nominate artists for reasons of urgent pragmatism. Artists have requirements to be quickly accepted by voters. Artists have social and financial capital so that winning works will be easier for artists to do than cadres who may need to work extra hard. So, artists were chosen because of their strategic position to collect votes for parties in the midst of tight competition in the 2019 election. In fact, candidates from among artists cannot always guarantee that they will be an effective means to boost vote acquisition. The popularity of artists is a major factor in political parties recruiting artists to become members of the legislature. This study shows that political parties do not carry out the functions of political parties properly. Artist popularity is a major factor in political parties recruiting artists to become members of the legislature. In this study, it can be seen that political parties do not carry out the functions of political parties properly. Therefore, researchers are interested in conducting research on this phenomenon. Keywords: Political Party, Artist.